AFEM Consensus Conference, 2013. AFEM Out-of-Hospital Emergency Care Workgroup Consensus Paper: Advancing Out-of-Hospital Emergency Care in Africa-Advocacy and Development - N.K. Mould-Millman; R. Naidoo; S. de Vries; C. Stein; L.A. Wallis (African Journal of Emergency Medicine, 2014)
Emergency care occurs on a continuum. Developing prehospital emergency care systems that are integrated with in-hospital emergency care systems can be a sustainable and effective way to help address the large morbidity and mortality of acute disease in Africa. Unfortunately, development of such prehospital systems across Africa has been slow to progress for many reasons, including feared cost implications, no agreed optimal system structure and function, and poor advocacy. In November 2013, the African Federation for Emergency Medicine (AFEM) convened a second expert and stakeholder meeting in Cape Town, South Africa, with the objective of reaching consensus on a few position statements to facilitate advocacy and to guide the development of emergency care in Africa. The objective of this paper is to report the outputs and position statements emerging from the AFEM Out-of-Hospital Emergency Care Workgroup consensus process. The term “Out-of-Hospital Emergency Care” was agreed by consensus and defined by the Workgroup as a suitable umbrella term for use in Africa that refers to the full spectrum of emergency care that occurs outside healthcare facilities. Critical components of this system were defined, including first responder care (tier-one) systems, and prehospital care and emergency medical services (tier-two) systems. The Workgroup provided a practical, adaptable and flexible set of guidelines and expert recommendations to facilitate advocacy and development of out-of-hospital emergency care systems in needy African settings. Future directions of the AFEM Out-of-Hospital Emergency Care Workgroup include creating an online Toolkit. This will serve as a repository of template documents to guide implementation and development of clinical care, education, transportation, public access, policy and governance.